The preventive role of environmental consultants and their importance in the environmental impact assessment process: update of latest regulatory changes - Queirolo Romero, Ana Paula (2018)
In Environmental Law, the regulation of the consultants and the regime to which they are subject is questioned. However, those who question it have not analyzed the fundamental role that they fulfill within the procedure that implies an environmental certification. Through this article, the author aims to explain the evolution of environmental consultants and demonstrate their role within the economic regime in Peru.